Exploring the Ontology of Surgical Procedures in the Read Thesaurus - Price, C.; O'Neil, M.; Bentley, T. E.; Brown, P. J. B. (Methods of Information in Medicine, 1998)
The Read Thesaurus is a comprehensive user-led clinical vocabulary developed from earlier, and structurally simpler, versions of the Read Codes, with substantial input from United Kingdom health care professionals. A constituent template table underpins a range of functions, including semantic definition of concepts using object-attribute-value triples. Concept representation for surgical procedures has been investigated by a number of groups and a standard European structure has been proposed. Over 50% ofthe surgical procedures in the Read Thesaurus have been fully characterised using a number of attributes each with a defined concept field. We report progress to date and, based on our large-scale experience, examine the applicability of the European model to a user-defined terminology.
Keywords: Clinical Vocabulary; Concept Definition; Terminology